Achieving high performance corrosion and wear resistant epoxy coatings via incorporation of noncovalent functionalized graphene. (April 2017) - Chen, Cheng; Qiu, Shihui; Cui, Mingjun; Qin, Songlv; Yan, Guoping; Zhao, Haichao; Wang, Liping; Xue, Qunji
Abstract: Graphene(G)-based polymer nanocomposites have attracted great interest owing to their superior physicochemical properties over polymers. However, the tendency of graphene sheets to aggregate makes it difficult to achieve homogenous dispersion in polymer matrix. Herein, by utilization of poly(2-butylaniline) (P2BA) as a dispersing agent, stable dispersion of graphene in organic solvents was achieved via non-covalent π-π interactions between P2BA and graphene nanosheets. The exfoliated graphene nanosheets were then integrated with coating matrix by curing reaction of epoxy resin with P2BA functionalized graphene (P2BA-G) and amine hardener. Embedding a small percentage of well-dispersed graphene nanosheets (P2BA0.5% -G0.5% ) in epoxy coating remarkably improved anticorrosion performance and wear resistance properties, which was attributed to the synergistic effects of the redox catalytic capability of P2BA, high mechanical and barrier properties of well-dispersed graphene nanosheets in the epoxy matrix. The present study provides a promise strategy for development of graphene reinforced organic coatings with superior physical-mechanical properties for metal protection. Graphical abstract: